Effects of National Literacy Remediation Program on The Reading Performance of Primary Grade Pupils - Mariano, Mayshell (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the effects of the National Literacy Remediation Program on the reading performance of primary grade pupils in selected public elementary schools in Tanay District, Schools Division Office of Rizal, during the School Year 2025–2026. The study utilized a descriptive survey research design and documentary analysis. Respondents included the total population of 104 primary grade teachers from eleven public elementary schools, while reading performance data were obtained from 220 primary grade pupils using the Comprehensive Rapid Literacy Assessment (CRLA). A researcher-made questionnaire-checklist was employed to measure teachers’ perceptions regarding the extent of the program’s effects in terms of phonemic awareness, fluency, and comprehension.Findings revealed that most teacher-respondents were 31 years old, female, married, pursuing graduate studies, holding Teacher I or Teacher II positions, with more than 15 years of teaching experience, and having attended various in-service trainings. The National Literacy Remediation Program was perceived to have a very high effect on phonemic awareness and a high effect on fluency and comprehension. Teachers’ perceptions did not significantly differ when grouped according to age, sex, civil status, educational attainment, length of service, position title, and in-service trainings attended. Based on CRLA results, most pupils were categorized under light refresher and moderate refresher levels, indicating progress toward grade-level readiness. Moreover, a significant relationship was found between pupils’ reading performance and the perceived effects of the program.The study concluded that teacher-related profile variables do not significantly influence perceptions of the program’s effects, while reading performance is significantly associated with the perceived effectiveness of the intervention. Continuous implementation of reading intervention programs, sustained professional development, systematic assessment, and adoption of the proposed action plan were recommended.
Keywords: National Literacy Remediation Program, reading performance, phonemic awareness, fluency, comprehension, primary grade pupils, reading intervention.